Managing Innovation in Highly Restrictive Environments Lessons from Latin America and Emerging Markets - Cortés-Robles, Guillermo; García-Alcaraz, Jorge Luis.; Alor-Hernández, Giner; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the integration of new tools, the modification of existing tools, and the combination of different tools and approaches to create new technical resources for assisting the innovation process. It describes the efforts deployed for assisting the transformation of Product-Services Systems and explains the main key success factors or drivers for success of each tool or approach applied to solve an innovation problems. The book presents a set of case studies to illustrate the application of several tools and approaches, mainly in developing countries. .
Against the odds. Innovation in Latin-American SMEs -- Use of Lean-Sigma as a problem-solving method in a restrictive environment -- Creation of Technology-Based Companies: Challenges to Innovate in the Manufacturing Sector of Medical Devices, the Case of Baja California, México -- Applying Action-research to academic patent-licensing path -- Mass customization process in companies from the housing sector in Brazil -- A Talent Management Model for Innovation and Competitiveness in Complex Domains: a study case in the Latin American energy sector -- The Role of ICT in Educational Innovation -- A Series of Recommendations for Industrial Design Conceptualizing Based on Emotional Design -- Indexing and Mapping Examples of Heuristics Compiled from TRIZ -- The use of affective computing in the conceptual design stage of new products -- Taking Advantage of the Innovation in Die Service Design -- TRIZ evolution trends as an approach for predicting the future development of the technological systems in the food industry -- A Service Design Process based on the Business Model Canvas and the C-K Theory -- Integration of Design Thinking and TRIZ theory to assist a user in the formulation of an innovation project. .
Keywords: Industrial engineering; Production engineering; Technological innovations; Engineering design; Industrial and Production Engineering; Innovation and Technology Management; Engineering Design